Answer:
x equals 2
Explanation:
Simplifying
8x + 4 = 13x + -6
Reorder the terms:
4 + 8x = 13x + -6
Reorder the terms:
4 + 8x = -6 + 13x
Solving
4 + 8x = -6 + 13x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13x' to each side of the equation.
4 + 8x + -13x = -6 + 13x + -13x
Combine like terms: 8x + -13x = -5x
4 + -5x = -6 + 13x + -13x
Combine like terms: 13x + -13x = 0
4 + -5x = -6 + 0
4 + -5x = -6
Add '-4' to each side of the equation.
4 + -4 + -5x = -6 + -4
Combine like terms: 4 + -4 = 0
0 + -5x = -6 + -4
-5x = -6 + -4
Combine like terms: -6 + -4 = -10
-5x = -10
Divide each side by '-5'.
x = 2
Simplifying
x = 2